2013
DOI: 10.1016/j.anbehav.2013.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Ambient temperature influences birds' decisions to eat toxic prey

Abstract: Aposematic prey warn predators of their toxicity using conspicuous signals. However, predators regularly include aposematic prey in their diets, particularly when they are in a poor energetic state and in need of nutrients. We investigated whether or not an environmental factor, ambient temperature, could change the energetic state of predators and lead to an increased intake of prey that they know to contain toxins. We found that European starlings, Sturnus vulgaris, increased their consumption of mealworm, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 67 publications
2
31
0
Order By: Relevance
“…Mammalian herbivores must balance the physiological challenges of detoxifying PSCs in their diet with thermoregulation to maintain homeostasis; both these functions are critical roles played by the liver [39]. Temperature-dependent toxicity may also impact other endotherms facing similar physiological challenges, such as omnivorous European starlings [40]. Furthermore, these effects could be size-dependent; smaller mammals inherently have higher energetic costs than their larger counterparts, but can dissipate heat more readily [31].…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian herbivores must balance the physiological challenges of detoxifying PSCs in their diet with thermoregulation to maintain homeostasis; both these functions are critical roles played by the liver [39]. Temperature-dependent toxicity may also impact other endotherms facing similar physiological challenges, such as omnivorous European starlings [40]. Furthermore, these effects could be size-dependent; smaller mammals inherently have higher energetic costs than their larger counterparts, but can dissipate heat more readily [31].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with European starlings ( Sturnus vulgaris ) suggest they can distinguish not only undefended from toxic prey, but also different levels of chemical defences, via taste‐rejection (Skelhorn & Rowe, , ), as well as gaining nutritional information about the prey (Skelhorn et al, ). This allows them to make educated decisions while foraging, depending on their motivation to feed; accordingly, starlings are more willing to consume defended prey when their own reserves are experimentally reduced (Barnett, Bateson & Rowe, ), early‐life or current conditions are harsher (Chatelain, Halpin & Rowe, ; Bloxham et al, ), or the prey have greater nutritional value relative to their toxicity (Halpin, Skelhorn & Rowe, ; Smith, Halpin & Rowe, ). While there is a growing body of evidence, primarily from laboratory experiments, suggesting that varying levels of motivation affect prey choice by predators, how this may impact the survival of aposematic prey and selection pressures on signal form in the wild is not yet clear.…”
Section: Predation and Signal Variationmentioning
confidence: 99%
“…Multiple studies have shown that higher temperatures interact with mammalian physiology in a way that results in increased toxicity of foreign compounds (Aldrich, Paterson, Tate, & Kerley, ; Dearing, ; Gordon, ; Keplinger et al., ). Evidence of TDT has been documented in laboratory rats (Gordon, ; Gordon et al., ), cattle (Aldrich et al., ; Spiers et al., ), birds (Chatelain, Halpin, & Rowe, ) and woodrats (Dearing et al., ; Kurnath & Dearing, ). When provided with temperature options, animals challenged with toxins chose cooler ambient temperatures (Gordon et al., ) and ingest greater proportions of nontoxic diets at warmer temperatures (Chatelain et al., ; Dearing et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of TDT has been documented in laboratory rats (Gordon, ; Gordon et al., ), cattle (Aldrich et al., ; Spiers et al., ), birds (Chatelain, Halpin, & Rowe, ) and woodrats (Dearing et al., ; Kurnath & Dearing, ). When provided with temperature options, animals challenged with toxins chose cooler ambient temperatures (Gordon et al., ) and ingest greater proportions of nontoxic diets at warmer temperatures (Chatelain et al., ; Dearing et al., ). Furthermore, higher temperatures reduce drug clearance times in both laboratory rats and woodrats, which is indicative of decreased liver function (Kaplanski & Ben‐Zvi, ; Kurnath & Dearing, ).…”
Section: Introductionmentioning
confidence: 99%